Time to steroids impacts visual outcome of optic neuritis in MOGAD. Issue 4 (13th December 2022) - Rode, Julie; Pique, Julie; Maarouf, Adil; Ayrignac, Xavier; Bourre, Bertrand; Ciron, Jonathan; Cohen, Mikael; Collongues, Nicolas; Deschamps, Romain; Maillart, Elisabeth; Montcuquet, Alexis; Papeix, Caroline; et al.
Abstract : Background: To characterise the response to treatment of inaugural optic neuritis (ON) in patients with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Methods: We searched the French MOGAD database for adults with inaugural ON with a detailed report of acute treatment modalities and measures of high-contrast best-corrected visual acuity (BCVA) at nadir and after 3 months. Predictors of visual outcomes were assessed by multivariable analysis. Results: Among 245 patients with at least one episode of ON, 82 fulfilled all criteria, and data on the peripapillary retinal nerve fibre layer (pRNFL) were available for 44. All patients received methylprednisolone (MP), combined with plasma exchange in 18. After 3 months, 75 of 82 (91%) patients retained full BCVA recovery, and median (range) pRNFL of the affected eye was 72 µm (40–102). Failure to regain 0.0 logarithmic minimum angle of resolution vision (Snellen 20/20) at 3 months was associated with time to first MP treatment ≥10 days (OR 16, 95% CI 1.14 to 213, p=0.01). pRNFL thickness after 3 months was related to better BCVA at nadir and time to first MP treatment <10 days (r2=19%, p=0.004 and r2=11%, p=0.03, respectively). Conclusions: Time to MP affects functional but also structural visual outcomes of ON in MOGAD.